Keeping Law Enforcement Connected - Gordon IV, John; Wallace, Brett Andrew; Tremblay, Daniel; Hollywood, John (RAND Corporation, 2023)
The National Institute of Justice strives to assist criminal justice practitioners through research, development, and evaluation of technologies and methods. RAND researchers interviewed an extensive sample group to assess priorities at the state and local levels, the means by which those agencies commonly receive information on technology, and the effectiveness of outreach by the National Law Enforcement and Corrections Technology Center.